Effect of Price Perception and Service Quality on on Purchase Decisions - Hazrati Havidz, Hazimi Bimaruci (Dinasti Publisher, 2022)
The Literature Review article on the Effect of Price Perception and Service Quality on Purchase Decisions is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Price Perception has an effect on Purchase Decisions; and 2) Service Quality has an effect on Purchase Decisions. Apart from these 2 exogenous variables that affect the endogenous variable of Purchase Decision, there are still many other factors including Price, Product Quality and Place variables.